Vulnerability assessment of agricultural drought hazard: a case of Koti-Se-Phola Community Council, Thabana Morena, Mafeteng District in Lesotho - Hlalele, Bernard Moeketsi (University of the Free State, 2014)
Over 80% of Lesotho populations' livelihood is dependent on rain-fed agriculture, and during droughts communities suffer most from the drought impacts. This study's main focus was to assess vulnerability to agricultural drought at Koti-Se-Phola Community Council (CC) in order to determine the conditions ofvulnerability and who and what is exposed to drought, to examine coping mechanisms used against drought and to provide relevant decision makers with information on drought for effective interventions. The study followed both quantitative and qualitative methodology where 5 villages were sampled in the study. The selected sample comprised of both working and non-working respondents. The total sample size considered in this study was 102. Questionnaires were distributed to household heads. An interview was held with agriculture official at Agriculture Project at Ha Bofihla for an expert opinion and to validate responses from household members. Data was entered in Microsoft Excel for analysis and SPSSV16 for reliability testing, the Cronbach alpha coefficient was found to be 0.764. From the selected drought indicators, a composite vulnerability index was established. Main findings of this study were that this community council was found to be vulnerable to drought with emerging issues such as high unemployment, elderly residents whose alternative income is old-age pension at M450 a month. Government responses to drought were found to be inadequate. Very few livestock especially cows were used for draught power in ploughing. However, many have devised means to cope with drought, through stockpiling of maize stalks, feeding of lekhale and torofeiye as well as chicken droppings to cows during droughts. Socially, some members have been sent away for job seeking and others picked up piece jobs as shepherds to reduce food consumption and pressures in the families. The general Agricultural Vulnerability Index was 0.4874. Suggestions were made by the respondents that employment-generating and poverty alleviation projects be put in place such as, the installation of irrigation systems at Makhaleng River and agricultural conservation projects to harness soil erosion. Given the current drought vulnerability situation, the researcher strongly recommends diversified livelihoods such as increased agricultural conservation where unskilled community members would earn a living in dry spells.
Dissertation (M.Sc. (Disaster Management))--University of the Free State, 2014
Keywords: Agricultural drought; Vulnerability; Disaster; Coping capacity